A simple method of computing the sample size for Chi-square test for the equality of multinomial distributions - Nisen, Jeffrey A.; Schwertman, Neil C. (Computational statistics & data analysis, 2008)
Computing the appropriate sample size is one of the most important aspects of designing an experiment. For the Chi-square test of the equality of multinomial populations a very simple method is proposed for calculating the sample size to satisfy specified significance level and power. This method is especially understandable and does not require software nor the non-central Chi-square tables. Simulations are used to verify the accuracy of the new method.